Na-ion mobility in P2-type Na0.5MgxNi0.17−xMn0.83O2 (0 ≤ x ≤ 0.07) from electrochemical and muon spin relaxation studies. Issue 42 (26th October 2021) - Ma, Le Anh; Palm, Rasmus; Nocerino, Elisabetta; Forslund, Ola Kenji; Matsubara, Nami; Cottrell, Stephen; Yokoyama, Koji; Koda, Akihiro; Sugiyama, Jun; Sassa, Yasmine; Månsson, Martin; Younesi, Reza
Abstract : The combination of electrochemical techniques and μ + SR helps to shed light on the Na-ion mobility in manganese-based cathode materials for sodium-ion batteries. Abstract : Sodium transition metal oxides with a layered structure are one of the most widely studied cathode materials for Na + -ion batteries. Since the mobility of Na + in such cathode materials is a key factor that governs the performance of material, electrochemical and muon spin rotation and relaxation techniques are here used to reveal the Na + -ion mobility in a P2-type Na0.5 Mg x Ni0.17− x Mn0.83 O2 ( x = 0, 0.02, 0.05 and 0.07) cathode material. Combining electrochemical techniques such as galvanostatic cycling, cyclic voltammetry, and the galvanostatic intermittent titration technique with μ + SR, we have successfully extracted both self-diffusion and chemical-diffusion under a potential gradient, which are essential to understand the electrode material from an atomic-scale viewpoint. The results indicate that a small amount of Mg substitution has strong effects on the cycling performance and the Na + mobility. Amongst the tested cathode systems, it was found that the composition with a Mg content of x = 0.02 resulted in the best cycling stability and highest Na + mobility based on electrochemical and μ + SR results. The current study clearly shows that for developing a new generation of sustainable energy-storage devices, it is crucial to study and understand both the structure as well as dynamics of ions in the material on an atomic level.